La gastronomía traidicional: eje del empoderamiento de la mujer istmineña - Mosquera Mosquera, Marelys (Universidad Antonio Nariño, 2021)
Ancestral gastronomy is one of our richest and most beautiful cultural heritage and in favor of this tradition, Istmineña women from ancient times to today have carried it out with an overwhelming passion, assuming with it a role of leadership and economic empowerment since the times of our grandmothers until today. This traditional activity has been the main economic source of these women and, in them, they have developed their culinary skills; allowed to support their families from generation to generation to this day. From there arises the need to promote traditional gastronomy as a fundamental axis of the economic empowerment of Istmineña women, as great matrons of our community did in their time, among which unforgettable women such as Paulina, Ideliza, Nieves, Pilar and others who from This humble profession met in the market square offering their vast culinary experiences and from there they offered their services to the entire community.